Synergistic influence on microbial communities ascribed to copper and tetracycline during aerobic composting: Insights into bacterial and fungal structures - Cui, Hu; Wang, Lixia; Zhang, Jian (Frontiers in Ecology and Evolution, 2022)
There are a considerable number of discussions aimed at analyzing microbial communities and their functions during the composting process. However, microbial succession under copper (Cu) and tetracycline (TCH)-stressed conditions has received less attention. Thus, this work analyzed the bacterial and fungal structures with high-throughput sequencing in Cu/TCH-amended composting (Cu: 0, 100, and 500 mg/kg; TCH: 0, 50, and 300 mg/kg), and the dominating controls on microbial diversity were identified using redundancy analysis (RDA) and structural equation models (SEMs). Low-concentration Cu increased the peak temperature (57°C) at the thermophilic phase. Composting phase-derived changes in bacterial and fungal communities were significant, while Cu and TCH showed a remarkable influence on fungi but not on bacteria. Cu and TCH inhibited Firmicutes' activity while promoting Actinobacteriota growth. Low-concentration Cu and TCH had a negative effect on Basidiomycota in the thermophilic phase and a positive influence on Chytridiomycota in the mature phase. TOC and TN were primary controls on the changes in microbial communities. NH4+-N and NO3--N were more beneficial to fungi with a contribution proportion of 42.13 and 16.85%, respectively. These findings could provide theoretical guidance for the directional research on microbial inoculants.